Metagenomic Insights Into the Microbial Assemblage Capable of Quorum Sensing and Quorum Quenching in Particulate Organic Matter in the Yellow Sea - Su, Ying; Yang, Yuanzhi; Zhu, Xiao-Yu; Zhang, Xiao-Hua; Yu, Min (Frontiers in Microbiology, 2021)
Quorum sensing (QS) is a density-dependent communicating mechanism that allows bacteria to regulate a wide range of biogeochemically important processes, and could be inhibited by quorum quenching (QQ). Increasing researches have demonstrated that QS affected the degradation of particulate organic matter (POM) in the photic zone. However, knowledge of the diversity and variation of microbial QS and QQ systems in sinking POM is scarce. Here, POM samples were collected from surface seawater (SW), bottom seawater (BW) and surficial sediment (SS) in the Yellow Sea of China. 16S rRNA gene amplicon and metagenome sequencing were performed to analyze the community structure of particle associated microorganisms and distribution of QS genes (acylated homoserine lactone (AHL) synthesizing gene luxI and AHL sensing gene luxR) and QQ genes (genes encoding for AHL lactonase and acylase) in POM. Shifting community structures were observed at different sampling depths, with an increasement of microbial abundance and diversity from SW to BW. Along with the variation of microbial communities, the abundance of luxI decreased with depth, while that of LuxR, AHL lactonase and acylase increased dramatically in SS. According to the taxonomic assignment and phylogenetic analyses, the horizontal transfer of QS and QQ genes existed in POM microbiota, which might be the key factor leading to the prevalence of the microbial communicating mechanisms in marine ecosystems. Moreover, the vertical transmission of QS and QQ genes were observed along with the microbial migration by sinking POM. Overall, our results increase the current knowledge of QS and QQ metabolic pathways in marine environment, and shed light on the intertwined interspecies relationships to better investigate their dynamics and ecological roles in POM cycling.